Between export-led growth and administrative Keynesianism: Italy's two-tiered growth regime - Donato Di Carlo; Andrea Ciarini; Anna Villa (Max Planck Institute for the Study of Societies, 2024)
Comparative political economy scholarship struggles to categorize Italy's model of capitalism between a mixed-market economy and a hybrid, stagnant economic system. To enhance our understanding of the Italian political economy, this paper employs the analytical framework of growth regimes to study Italy's regional economic systems. Our analysis indicates that Italy can hardly be defined as a "national growth regime" due to the presence of two diametrically opposed regional growth regimes: northern regions conform to a manufacturing-based, export-led growth regime supported by competitiveness-enhancing territorial institutions; southern regions conform to a particular variety of the consumption-led growth regime, that is, an administrative Keynesianism regime, which we theorize to typify a regime where growth and employment are systematically dependent on the state's role as employer of last resort, the state's consumption-enhancing social policies, and economic forbearance of labor and corporate tax regulations. The paper suggests that studying regional growth regimes is desirable when marked internal diversity in economic outcomes or productive structures exists across regions within (generally larger) countries, and when subnational governments have powers to develop their own major institutions/policies in support of regional growth regimes. – – Die Vergleichende Politische Ökonomie tut sich schwer mit einer Kategorisierung des italienischen Kapitalismusmodells, das irgendwo zwischen einer gemischten Marktwirtschaft und einem hybriden, stagnierenden Wirtschaftssystem anzusiedeln ist. Um unser Verständnis der Politischen Ökonomie Italiens auszubauen, untersucht das Papier basierend auf der Wachstumsmodelltheorie Italiens regionale Wirtschaftssysteme. Die Analyse zeigt, dass Italien über zwei diametral entgegengesetzte Wachstumsmodelle verfügt: die nördlichen Regionen mit ihrer umfangreichen Industrieproduktion weisen die Charakteristika eines exportorientierten Wachstumsregimes auf, unterstützt durch wettbewerbsfördernde Institutionen; die südlichen Regionen hingegen entsprechen einer besonderen Variante eines konsumorientierten Wachstumsregimes, die wir administrativen Keynesianismus nennen, in dem Wachstum und Beschäftigung systematisch von der Rolle des Staates als Arbeitgeber letzter Instanz, von den konsumfördernden Effekten von Sozialpolitik und von arbeits- und unternehmenssteuerlichen Begünstigungen abhängen. Die Ergebnisse der Studie legen eine Analyse regionaler Wachstumsmodelle nahe, wenn Regionen (in generell größeren Ländern) eine ausgeprägte Vielfalt im Hinblick auf Wirtschaftskraft und Produktionsstrukturen aufweisen und wenn subnationale Regierungen in der Lage sind, eigene wichtige Institutionen und Regelungen durchzusetzen, um regionale Wachstumsregime zu stärken.
hdl:21.11116/0000-0010-0081-B
Keywords: 300; comparative economic systems; comparative political economy; growth models; Italy; regional economies; Italien; regionale Ökonomien; vergleichende politische Ökonomie; vergleichende Wirtschaftssysteme; Wachstumsmodelle